Characteristics of Antibiotic-Resistant Bacteria in Libya Based on Different Source of Infections - Hosien, Bushra; Belhaj, Howida; Atia, Ahmed (Libyan International Medical University Journal, 2022)
In recent years and for decades, antimicrobial resistance (AMR) has expanded into a major clinical issue. Infections were no longer a life-threatening issue for clinicians after the discovery of antibiotics. The misuse or overuse of antibiotics, however, contributes to global AMR, and numerous mobile genetic elements and relevant resistant genes worsen the spread of resistance. As antibiotics lose their effectiveness, a growing number of infections such as pneumonia, tuberculosis, and gonorrhea are getting harder and sometimes impossible to treat. Infections that are resistant to antibiotics are correlated with antibiotic misuse. The majority of the antibiotic resistance in microbes is caused by improper use of antibiotics. Because there are a few antibiotics available to treat multidrug-resistant bacterial infections, there is a high rate of morbidity and mortality. Libya has a high burden of antibiotic resistance, and antimicrobial malpractice has frequently been reported. Providing information on the current state of antimicrobial resistance in Libya may assist the health authorities in addressing the problem more effectively in the future. Therefore, this review highlights the current situation of bacterial profile and their antimicrobial resistance in Libya based on the source of infection. Articles related to the topic were searched using databases and search engines such as PubMed, Google Scholar, and ResearchGate websites. These articles were selected if they were conducted in Libya and provided information on bacterial pathogens and AMR. Required data were extracted for the purpose of this review report, and then further verified for identifying the prevalence and number of susceptible and resistant pathogens in each source of infection.
Keywords: bacteria; antibiotic; microbial resistance; infection; Libya